Legal Fictions in Theory and Practice - Del Mar, Maksymilian; Twining, William (Law and Philosophy Library,, 2015)
This multi-disciplinary, multi-jurisdictional collection offers the first ever full-scale analysis of legal fictions. Its focus is on fictions in legal practice, examining and evaluating their roles in a variety of different areas of practice (e.g. in Tort Law, Criminal Law, and Intellectual Property Law), and in different times and places (e.g. in Roman Law, Rabbinic Law, and the Common Law). The collection approaches the topic in part through the discussion of certain key classical statements by theorists including Jeremy Bentham, Alf Ross, Hans Vaihinger, Hans Kelsen and Lon Fuller. The collection opens with the first-ever translation into English of Kelsen's review of Vaihinger's As If. The 17 chapters are divided into four parts: 1) a discussion of the principal theories of fictions, as above, with a focus on Kelsen, Bentham, Fuller and classical pragmatism; 2) a discussion of the relationship between fictions and language; 3) a theoretical and historical examination and evaluation of fictions in the common law; and 4) an account of fictions in different practice areas and in different legal cultures. The collection will be of interest to theorists and historians of legal reasoning, as well as scholars and practitioners of the law more generally, in both common and civil law traditions.